Current trends and future directions of hydroponics in urban agriculture: A competent technology for food production and wastewater management - Chaurasia, Shardesh Kumar; Sharma, Navdeep (Journal of Scientific Agriculture, 2025)
The surge in the global population foresees a significant increase in the demand for food. Due to the scarcity of arable land and water resources crucial for agriculture, there is a shortfall in food production, posing a daunting challenge, nonetheless. Specific technological advancements in agriculture must be integrated to mitigate this pressing issue. These technologies aim to conserve or recycle water, positively influencing food production and accessibility. One such technology is hydroponics, which operates without soil and minimizes water consumption. It efficiently uses horizontal and vertical space, demonstrating the potential to generate higher yields than traditional farming methods. Its global traction stems from its ability to optimize resource management, facilitate year-round crop cultivation, and reduce susceptibility to pest infestations. In addition, hydroponics gains a notable edge over conventional farming techniques by offering the capability for real-time monitoring of environmental variables. Alleviating the strain on agricultural resources and bolstering food security on a global scale is a promise that the adoption of hydroponics holds, as a result.